Effect of inhaled thiorphan, a neutral endopeptidase inhibitor, on the bronchodilator response to inhaled atrial natriuretic peptide (ANP). (January 1996) - Angus, R. M.; Millar, E. A.; Chalmers, G. W.; Thomson, N. C.
Abstract : BACKGROUND: The hormone atrial natriuretic peptide (ANP) causes bronchodilation and partially protects against direct and indirect bronchial challenges. Both in vitro and in vivo studies have found that the protective effect of ANP against bronchoconstriction is enhanced by inhibition of the enzyme neutral endopeptidase (NEP). It was hypothesised that pretreatment with thiorphan, an NEP inhibitor, might enhance the bronchodilator response to inhaled ANP. METHODS: In a randomised double blind placebo controlled crossover study, six asthmatic patients (one woman) of mean (SD) age 47.3 (3.8) years and forced expiratory volume in one second (FEV1) 1.91 (0.42) 1, 55 (3.8)% predicted, were studied. All were shown at screening to have at least a 25% improvement in FEV1 to inhaled salbutamol. On five study visits the patients received either thiorphan 1 mg (in 2 ml) followed by ANP 5 mg or placebo (saline), or placebo (saline) followed by ANP (5 mg), placebo or salbutamol 5 mg. Spirometric parameters were measured after each inhalation and thereafter for the next two hours. RESULTS: ANP alone caused a bronchodilator response up to 15 minutes when compared with placebo or thiorphan alone with a mean (SE) change in FEV1 of 16.8 (8.1)% and 16.1 (6.8)% at 10 and 15 minutes from baseline, respectively. Prior inhalation of thiorphan prolonged the duration of the bronchodilator effect of ANP up to 60 minutes with a mean (SE) change in FEV1 of 23.1 (3.4)% at 60 minutes. There was no difference in the maximum degree of bronchodilation following the administration of ANP alone compared with the combination of thiorphan and ANP. The degree and duration of the bronchodilator response produced by ANP, or the combination of the NEP inhibitor and ANP, were less than that produced by salbutamol. CONCLUSIONS: These results confirm that, at least in part, the bronchodilator response to inhaled ANP is modulated by NEP. Analogues of ANP which are stable to NEP may have greater bronchodilator activity than ANP in the treatment of asthma.